Students' Motivation towards Learning Physical Education Sports and Health at Elementary School - Geby; Yashinta; Enney; Gabriel; Fajar (Outline Publisher, 2024)
Using a qualitative approach, this study examined students' motivation to learn Physical Education, Sport and Health (PJOK) in primary schools. This study used a qualitative approach with in-depth interview techniques and participatory observation to collect data from teachers and students in elementary schools. Semi-structured interviews were conducted to find out students' perceptions, attitudes and experiences related to learning PJOK. The main objective of this research is to identify and understand students' motivation towards learning Physical Education, Sports and Health (PJOK) in elementary schools. In addition, this study also sought to explore students' perceptions, attitudes and experiences related to learning PJOK, such as the classroom environment, teacher support and learning methods. The results show that students' motivation is the main factor influencing their participation and learning achievement in the subject. In addition, the results show that positive interactions between students and teachers, as well as interesting and interactive learning approaches, contribute significantly to increasing students' motivation. This study concludes that, to increase students' motivation in learning PJOK, teachers and schools must provide continuous support. It is hoped that these findings will help teachers and policy makers create better and more engaging PJOK programs for primary school students.